THE INFLUENCE OF WORKLOAD AND COMPENSATION ON STUDENT WORK SATISFACTION IN CERTIFIED INTERNSHIP & INDEPENDENT STUDY PROGRAM (MSIB) CLASS 3 PT. INKA MULTI SOLUSI SERVICE IN THE CITY OF MADIUN - Azis, Muh Ilham; ] Idris, Abdi Akbar; Ruma, Zainal; Sahabuddin, Romansyah; Burhanuddin (Transpublika Publisher, 2023)
Workload refers to the volume and intensity of tasks and responsibilities assigned to interns during their internship period. It encompasses the amount of work, deadlines, complexity, and the level of autonomy given to students. Compensation, on the other hand, refers to the monetary or non-monetary benefits provided to interns for their work. This study aims to determine the effect of workload on job satisfaction, the effect of compensation on job satisfaction, and the effect of workload and compensation on student job satisfaction in the Certified Independent Study & Internship Program (MSIB) Batch 3 PT. INKA Multi Solusi Service in Madiun City. The study utilizes quantitative data obtained from questionnaires distributed to 35 participants. The data were analyzed using the simple linear regression analysis method with the help of SPSS for data processing to prove the hypothesis. The results indicate that the workload variable has a significant negative effect on job satisfaction, meaning that higher workloads are associated with lower job satisfaction. Conversely, the compensation variable has a significant positive effect on job satisfaction, meaning that higher compensation leads to higher levels of job satisfaction. Simultaneously, the variables of workload and compensation show a significant combined effect, suggesting that lower workloads and higher compensation result in higher job satisfaction among students in the 3rd batch of the Certified Independent Study & Internship Program PT. INKA Multi Solusi Service in Madiun City.